Metaphor and Metonymy according to functionalist approach: the study of grammaticalization of the É QUE - Gomes, João Bosco Figueiredo (2016)
There is a growing spoken and written use of the expression é que named " expletive " both in the Brazilian and European Portuguese. This paper reports the results of an empirical investigation of the emergence use of the expression é que. It aims at presenting the processes/mechanisms that characterize the emergence use of the expression é que as related to a process of grammaticalization. From a functionalist paradigm in which the study of grammaticalization is situated, the study analyzes, diachronically, written sample data since the ancient Portuguese. The empirical results seem to confirm the hypothesis that the one-way path to the change of the expression é que had, in the early stages of grammaticalization a semantic-pragmatic motivation OBJECT/ SPACE > TEXT, including a mechanism of metoymy by means of a reanalysis of the 13th century original use of é o que in the expression é que.